Life quality among elderly with obesity in outpatient clinic, dr. Soetomo hospital, surabaya - Kurniawati, Patricia Maria; Laswati, Hening Laswati (Folia Medica Indonesiana, 2017)
Obesity is one of the chronic diseases that may have significant impact and affect the quality of life, especially in elderly who already have multidimensional problems. This study aimed to provide information about the influence of obesity in elderly on every component of his quality of life by using the SF-36 quality of life. This study was conducted on 105 patients in outpatient Medical Rehabilitation, Geriatrics and Diabetes at Dr. Soetomo Hospital, Surabaya. Patients aged 60-75 years, consisting of 62 men and 43 women. The number of patients with obesity was 49 persons (46.7%) with an average body mass index (BMI) of 27.16 kg / m2. Whereas, non-obese patients were 56 persons (53.3%) with an average BMI of 21.23 kg/m2. In conclusion, there was no significant difference in the SF-36 life quality of obesity and non-obesity groups after being analyzed using t-test.